Reading Log to Promote Extensive Reading Activities: Students’ Perspective - Tiara Salsabila; Pratnyawati Nuridi Suwarso; Devinta Puspita Ratri; Rifa Utmawati (Journal of English Language and Education, 2021)
Reading log serves a crucial function in extensive reading by reminding students to read and encouraging them to record all they have read. However, some argue that keeping a reading log might be a burden for students and reduce their reading passion. Therefore, this study aims at figuring out students' perceptions and experiences with reading logs in order to help them with their extensive reading. This study involved 100 high school students who were equally assigned to do extensive reading activities outside of school hours for six weeks. The research data were collected through the questionnaire to find out student perspectives about extensive reading, the benefit, and difficulties when doing extensive reading activities using a reading log. Although the students had some difficulties, however, after data analysis, it was found that the students' perspective on extensive reading activity using a reading log was good.